Addressing social influences reduces antibiotic duration in complicated abdominal infection: a mixed methods study. Issue 1 (6th March 2018) - Broom, Jennifer; Tee, Chin Li; Broom, Alex; Kelly, Mark D.; Scott, Tahira; Grieve, David A.
Abstract : Background: Antimicrobial therapy for intra‐abdominal infections is often inappropriately prolonged. An intervention addressing factors influencing the duration of intravenous antibiotic use was undertaken. This study reports the antibiotic prescribing patterns before and after the intervention and a qualitative analysis of the experience of the intervention. Methods: Quantitative : A retrospective audit of patients with complicated intra‐abdominal infection before and after a multifaceted persuasive intervention was performed. Qualitative : Semi‐structured interviews were performed to evaluate which elements of the intervention were perceived to be effective. Results: An intervention including collaborative inter‐specialty and inter‐professional educational meetings, and education of all professional streams was undertaken. Quantitative : Twenty‐three patients before and 22 patients after the intervention were included. The total duration of antibiotics decreased significantly following the intervention (9.2 versus 6.6 days P  = 0.02). The duration of intravenous antibiotics did not change significantly (5.4 versus 4.5 days, P  = 0.06). Qualitative : Eighteen health‐care professionals participated. Thematic analysis indicated that a collaborative approach between senior surgical and infectious disease specialists in the pre‐intervention stage led to perceived ownership and leadership of the intervention by the surgical team, which was thought critical to the success of the intervention. Conversely, the ability of nurses and pharmacists to influence antibiotic practice was considered limited and a poster promoting the intervention was perceived as ineffective. Conclusion: Consultant leadership and specialty ownership of the process were perceived to be critical in the success of the intervention. Antibiotic stewardship programs which address social factors may have greater efficacy to optimize antimicrobial prescribing.